Foreign language teacher competences as perceived by English language and literature students - Drakulić, Morana (Journal of Education Culture and Society, 2020)
This paper considers competences of the foreign language teacher in the Republic of Cro-atia. Despite the clear classifi cation of foreign language teacher competences on a primary level, which was developed within the TEMPUS project, no reliable instrument has yet been constructed to account for those competences. The purpose of my research was to investigate the metric characteristics of an instrument which could be useful for determining foreign language teacher competences in the Republic of Croatia. A questionnaire was applied to 126 study participants (bachelor and master English language and literature students). The fi nal version of the questionnaire consisted of eighteen items and four factors, which were extrac-ted using exploratory factor analysis. The results have shown that the developed instrument is not fully applicable to the Croatian foreign language learning context. Still, some of its aspects may be used in future instrument construction.